Antimicrobial efficacy of clindamycin, linezolid, and calcium hydroxide as root canal medicaments on tubular infection against Enterococcus faecalis biofilm: An in vitro study - Manisha Rani Bharathi; Mahima Tilakchand; Priya Horatti; Rideep Chaliha (Endodontology)
Aim: The aim of the study was to evaluate and compare the antimicrobial efficacy of linezolid, clindamycin, and calcium hydroxide (Ca(OH)2) as an intracanal medicament on Enterococcus faecalis biofilm. Methods: Fifty-six root blocks obtained from extracted single-rooted human teeth were decoronated, and the apical part of the root was removed to obtain a 6 mm cylinder of radicular dentin. The specimens were standardized for diameter, infected with microorganisms, and randomly divided into four groups. linezolid, clindamycin, Ca(OH)2, and methylcellulose (control) were placed in the root canal for 7 days. Dentin shavings were collected from 200 to 400 µm depth, and bacterial load was assessed by counting colony-forming units. Scores were statistically analyzed using the Kruskal–Wallis ANOVA and the Mann–Whitney test. Results: Linezolid and clindamycin had better antibacterial effects than control at both 200 µm and 400 µm depth after 7 days. Conclusion: Linezolid and clindamycin outperformed Ca(OH)2 in reducing bacteria and were equally efficient against E. faecalis but showed no significant differences in antimicrobial efficacy.